Correcting streamflow bias considering its spatial structure for impact assessment of climate change on floods using d4PDF in the Chao Phraya River Basin, Thailand - Budhathoki, Aakanchya; Tanaka, Tomohiro; Tachikawa, Yasuto (Journal of hydrology. Regional studies, 2022)
Chao Phraya River Basin (CPRB), the predominant basin located in Thailand. This study aims to ascertain the difference between spatial bias heterogeneity of streamflow in large river basins such as CPRB for a robust analysis. The upstream major dams and the outlet of the basin were examined with two-step bias correction and compared with a more practical bias correction only at the outlet of the basin. The former clarified that, due to the large effect of downstream bias, the upstream bias effect was considered negligible thus the two approaches resulted in similar future projections in the CPRB. Through this comparison, streamflow bias in the past and future climate experiments was corrected considering its spatial characteristics for robust assessments of quantitative impacts of climate change. A + 4 K warmer climate will increase the frequency of the 2011 flood in CPRB and enhance 100-year flood peak discharge by 1.1–1.6 times than the past climate (1961–2010). The future flood in the basin, which starts predominantly in September in the present climate, is likely to begin in September and August equally with a prolonged duration of floods around 10–50 days. The study region is likely expected to experience elevated flood volume, earlier flood occurrence, and longer flood duration which indicates that forthcoming floods will be more rigorous. [Display omitted] •Climate change impact assessment on floods in Chao Phraya River Basin.•Spatial streamflow bias correction of d4PDF datasets for + 4 K warming condition.•100-year flood to magnify by 1.1–1.6 times than the past climate.•Adaptation measures required with shift in start of flooding month.